Comparison of live and inactivated Salmonella Typhimurium vaccines containing different combinations of SPI-1 and SPI-2 antigens in poultry - K. Papezova; H. Havlickova; F. Sisak; V. Kummer; M. Faldyna; I. Rychlik (Veterinární Medicína, 2008)
Salmonella enterica subsp. enterica originating from poultry and poultry products is responsible for the vast majority of human gastrointestinal disorders in Europe. For this reason different measures that seek to decrease its incidence in poultry including vaccination with inactivated vaccine continue to be tested. In this study we compared four different inactivated vaccines of S. Typhimurium in chickens which were enriched by SPI-1 or SPI-2 proteins that are central to Salmonella virulence. Six-week-old chickens were intramuscularly vaccinated, revaccinated at 9 weeks and challenged at 12 weeks of age. For two weeks post challenge faecal shedding was monitored. There was no significant difference in the performance of the four compared inactivated vaccines and all of them decreased faecal shedding during the first weeks post infection by 10-1 000× when compared with non-immunized control chickens. However, the level of protection provided by inactivated vaccines was much lower when compared with a live vaccine based on a phoP rpoS double deletion S. Typhimurium mutant which was included as an additional control.